Redesigning Journal Clubs to Staying Current with the Literature - Roland N. Dickerson; G. Christopher Wood; Joseph M. Swanson; Rex O. Brown (MDPI AG, 2017)
Staying current with the literature is of paramount importance to the pharmacist engaged in an evidence-based clinical practice. Given the expanding roles and responsibilities of today's pharmacists combined with exponential growth in new medical and health sciences literature, staying current has become an extremely daunting task. Traditional journal clubs have focused upon their role as a training vehicle for teaching critical reading skills to residents. However, schools of pharmacy are now required to provide instruction in biostatistics, research design, and interpretation. We present a paradigm shift in the traditional journal club model whereby a collection of periodicals is screened and a short synopsis of the pertinent articles is provided. The associated tasks for screening and presenting of the primary literature are shared among a group of clinicians and trainees with similar practice interests resulting in a more reasonable workload for the individual. This journal club method was effective in identifying a significant majority of articles judged to be pertinent by independent groups of clinicians in the same practice arenas. Details regarding the shared core practice and knowledge base elements, journal club format, identification of journals, and evaluation of the success of the journal club technique are provided.